AI based medical imagery diagnosis for COVID-19 disease examination and remedy - Ashraf Aboshosha (Scientific Reports)
Abstract COVID-19, caused by the SARS-CoV-2 coronavirus, has spread to more than 200 countries, affecting millions, costing billions, and claiming nearly 2 million lives since late 2019. This highly contagious disease can easily overwhelm healthcare systems if not managed promptly. The current diagnostic method, Molecular diagnosis, is slow and has low sensitivity. CXR, an initial imaging tool, provides rapid results, but is less sensitive compared to CT scans. This article focuses on using AI for two main objectives: classifying the severity of COVID-19 and determining the appropriate treatment. Highlights key factors in the diagnosis and treatment of COVID-19, addressing questions such as: 1. For COVID-19 is innate immunity more important or acquired immunity? 2. Is the COVID-19 an immunity disorder or Acute Respiratory Distress Syndrome(ARDS)? 3. Is the cross mortality due to aging more dangerous than COVID-19? 4. Is COVID-19 a seasonal disease due to the deficiency of vitamin D in winter? 5. Is it better to treat COVID-19 as an epidemic or a pandemic?